Comparative Study Between Digital and Conventional Based Learning on Student Learning Outcomes at STKIP Hermon Timika - Tupen, Maria Letisia Lipat (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The development of information and communication technology (ICT) has brought significant changes to the field of education, including higher education. The shift from conventional learning methods to digital-based learning has become an inevitable global trend. Conventional methods still offer advantages in terms of direct interaction between lecturers and students, but they are increasingly facing challenges related to flexibility and accessibility. On the other hand, digital learning methods provide easier access, greater flexibility, and improved efficiency, yet they also encounter obstacles such as limited face-to-face interaction and inadequate infrastructure—particularly in remote areas.This study is a comparative analysis aimed at examining the differences in student learning outcomes between digital-based learning and conventional learning. A descriptive comparative method with a quantitative approach was employed to collect data from two groups of students, each consisting of 25 participants, who engaged in learning through both digital and conventional methods. The data collected included demographic information, learning outcomes, as well as students’ perceptions and satisfaction levels with both approaches. The data were analyzed statistically.The findings indicate that digital-based learning is significantly more effective in improving learning outcomes compared to conventional methods. Students who participated in digital learning achieved higher average final exam scores. However, there were variations in student perceptions and satisfaction levels between the two methods, reflecting unique preferences and challenges associated with each approach.